The Role of Psychological Capital Towards Work Engagement at Private University Lecturers in Bandung - Endah Andriani Pratiwi; Diana Harding; Marina Sulastiana; Efi Fitriana (AL-ISHLAH: Jurnal Pendidikan, 2024)
The objective of this study was to explore the role of psychological capital in work engagement among lecturers at private universities in Bandung. Utilizing a quantitative research methodology, the study involved 50 lecturers, comprising 36 men and 14 women. The Utrecht Work Engagement Scale (UWES) and the Psychological Capital Questionnaire (PCQ) were employed as instruments. Initially, the research involved an in-depth review of relevant literature. Following this, the scales were distributed to the participants, and the collected data were subjected to factor analysis. The analysis was conducted using SPSS 16 software, employing linear regression techniques. The findings indicate that psychological capital significantly influences work engagement, accounting for 46.1% of the variance. Specifically, the self-efficacy component contributes 24.8% to work engagement, the hope component contributes 34.0%, the optimism component contributes 40.5%, and the resilience component contributes 25.6%. These results suggest that psychological capital plays a crucial role in enhancing work engagement among lecturers at private universities in Bandung.